Telaah Literatur Potensi Lutein dari Bunga Marigold Lokal sebagai Suplemen Kesehatan - Jovine Marcella Kurniawan; Melisa Megawati Yusuf; Heriyanto Heriyanto; Tatas Hardo Panintingjati Brotosudarmo (Media Penelitian dan Pengembangan Kesehatan, 2020)
Abstract Lutein is a type of xanthophyll that accumulated predominantly in eye macula, and is distributed in several parts of the human body, such as skin and brain. Lutein accumulation in the human body is associated with the health benefits of lutein, including being an antioxidant and protecting, the eyes and skin from exposure to blue light, and playing an important role to maintain human cognitive health. Lutein cannot be synthesized by human, so consumption of lutein can be obtained from foods such as fruits and green vegetables, as well as from supplements. The purpose of writing this article was to increase awareness of the importance of adequate lutein intake early in the body, as well as increased research interest in exploring local resources as a potential source of lutein, the Mega Orange marigold from Bali as a raw material for health supplements. The potential lutein article as health supplement was prepared by reviewing articles from international journals and followed by testing the composition of carotenoids in Mega Orange marigolds and a health supplement product by HPLC analysis. Various studies and article publications regarding the health benefits of lutein have been found in the last decade. There are at least two main benefits of lutein, namely as an antioxidant and to maintain the health of organs such as the eyes, brain and skin. Meanwhile, the local marigold flower variety of Mega Orange contains carotenoids lutein and zeaxanthin up to 13.88 mg/g dry weight, and this result is in the range of lutein concentrations in marigold flowers that grow in Thailand. Mega Orange marigold is a potential source of lutein that can be used as raw materials for health supplement products. The importance of lutein intake for the human body makes the use of lutein from local marigolds in the manufacture of health supplements needs to be optimized and utilized. Abstrak Lutein termasuk jenis xantofil yang terakumulasi secara dominan pada makula, serta terdistribusi pada beberapa bagian tubuh manusia seperti kulit dan otak. Akumulasi lutein pada tubuh manusia dikaitkan dengan manfaat kesehatan lutein, diantaranya sebagai antioksidan serta melindungi mata dan kulit dari paparan sinar biru, dan memainkan peranan penting untuk menjaga kesehatan kognitif manusia. Lutein tidak dapat disintesis oleh manusia, sehingga konsumsi lutein dapat diperoleh dari makanan seperti buah dan sayuran hijau, serta dari suplemen. Tujuan penulisan artikel ini adalah untuk meningkatkan kesadaran akan pentingnya kecukupan asupan lutein sejak dini dalam tubuh, serta menambah minat penelitian akan eksplorasi sumber daya lokal yang sebagai sumber potensial lutein yaitu bunga marigold Mega Orange dari Pulau Bali sebagai bahan baku suplemen kesehatan. Artikel potensi lutein sebagai suplemen kesehatan ini disusun dengan menelaah artikel-artikel pada jurnal internasional dan diikuti dengan pengujian komposisi karotenoid pada bunga marigold Mega Orange dan satu produk suplemen kesehatan dengan analisis Kromatografi Cair Kinerja Tinggi (KCKT). Berbagai penelitian dan publikasi artikel mengenai manfaat kesehatan lutein telah banyak ditemukan dalam dekade terakhir. Setidaknya terdapat dua manfaat utama lutein, yaitu sebagai antioksidan dan untuk menjaga kesehatan organ tubuh seperti mata, kulit, dan otak. Adapun, bunga marigold lokal varietas Mega Orange mengandung karotenoid lutein dan zeaksantin hingga 13,88 mg/g berat kering, dan hasil ini berada pada rentang konsentrasi lutein dalam bunga marigold yang tumbuh di Thailand. Bunga marigold Mega Orange merupakan sumber potensial lutein yang dapat digunakan sebagai bahan baku produk suplemen kesehatan. Pentingnya asupan lutein bagi tubuh manusia menjadikan pemanfaatan lutein dari bunga marigold lokal dalam pembuatan suplemen kesehatan perlu dioptimalkan dan dimanfaatkan.